Alcohol and other psychoactive drugs in trauma patients aged 10–14 years. Issue 2 (1st June 1999) - Li, Guohua; Chanmugam, Arjun; Rothman, Richard; DiScala, Carla; Paidas, Charles N; Kelen, Gabor D
Abstract : Objective —To examine the prevalence of alcohol and/or other psychoactive drugs, such as marijuana and cocaine (AODs), involved in preteen trauma patients. Methods —Toxicological testing results were analyzed for 1356 trauma patients aged 10–14 years recorded in the National Pediatric Trauma Registry for the years 1990–95. Results —Of the 1356 patients who received toxicological screening at the time of admission, 116 (9%) were positive for AODs. AOD involvement increased with age. Patients with pre-existing mental disorders were nearly three times as likely as other patients to be AOD positive (23% v 8%, p<0.01). AOD involvement was more prevalent in intentional injuries and in injuries that occurred at home. Conclusions —AODs in preteen trauma are of valid concern, in particular among patients with mental disorders or intentional injuries. The role of AODs in childhood injuries needs to be further examined using standard screening instruments and representative study samples.